Il rumore nel suono (e nell’armonia). : Riflessioni su un’intuizione di Jean-Jacques Rousseau (De Musica, 2023)
Usually sound and noise, as well as harmony and noise, are mutually exclusive terms. In his polemic with Rameau, Rousseau challenges this opposition in principle and suggests that sound, noise, and harmony are more closely related than one might imagine. It is not just a matter of noting that harmony lends itself to the imitation of natural noises and that, in a broad sense, it is nothing more than noise (insofar as it is incapable of imitating the accents of the human voice); in more essential terms, Rousseau shows that in the sound produced by the vibration of a vibrating body — that is, in the very phenomenon on which Rameau had intended to base harmonic theory — there is already noise. By commenting on the Rousseauian text, this article aims to show in what sense this insight comes to be in line with the project of exploring the sound pursued by spectralists in the twentieth century. It also highlights in what sense Rousseau’s insight cannot be considered as a true anticipation, being based on a more static (and typically eighteenth-century) conception of the musical object.